An inexpensive and simple 3-D-motion capture procedure - Mikl, J. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
Commercial motion capture systems that are expensive, require permanent fixing, or require large and/or cumbersome calibration frames can preclude the use of video analysis in a training environment. Using inexpensive high-speed cameras, a checkerboard, and free open-source software a procedure was determined to achieve good motion-tracking accuracy for the study of divers at a pool. This procedure will be used in future studies, and may also be of use to other researchers with limited budgets.